Fundación P.I.D.E.E. : [archive] ([Microfilmed for] Fundación P.I.D.E.E. [by COMICROM] ; [Available from Latin American Microform Project, Center for Research Libraries], 2004)
Records from PIDEE archive in Santiago, Chile. Consists of case files for children and families to whom services were supplied by PIDEE. Case files are arranged arranged as follows: Section I. Missing detainees; Section II. Persons executed for political reasons; Section III. Political prisoners; Section IV. Former political prisoners; Section V. Persons returning from exile; Section VI. Family reunification; Section VII. Persons subject to restricted residence order; Section VII. Special cases (persecutions, threats, or others)